Inflammatory Processes Triggered by Helicobacter pylori Infection Cause Aberrant DNA Methylation in Gastric Epithelial Cells - Niwa, Tohru; Tsukamoto, Tetsuya; Toyoda, Takeshi; Mori, Akiko; Tanaka, Harunari; Maekita, Takao; Ichinose, Masao; Tatematsu, Masae; Ushijima, Toshikazu (Cancer research (Chicago, Ill.), 2010)
Altered patterns of DNA methylation associated with Helicobacter pylori (HP) infection of gastric epithelial cells are thought to contribute to gastric cancer risk. However, it is unclear whether this increased risk reflects an infection-associated inflammatory response or the infection itself. In this study, we sought to clarify mechanisms in a gerbil model of gastric cancer where we showed that HP infection is causally involved in induction of aberrant DNA methylation. By genome-wide screening, CpG islands that were aberrantly methylated in gerbil gastric cancer cell lines were isolated, and 10 islands were shown to be specifically methylated only in gastric mucosae infected with HP. By temporal analysis, methylation levels in gastric epithelial cells started to increase at 5 to 10 weeks after infection and reached high levels by 50 weeks. When HP was eradicated, methylation levels markedly decreased 10 and 20 weeks later, but they remained higher than those in gerbils that were not infected by HP. Expression levels of several inflammation-related genes (CXCL2, IL-1β, NOS2, and TNF-α) paralleled the temporal changes of methylation levels. Significantly suppressing inflammation with the immunosuppressive drug cyclosporin A did not affect colonization by HP but blocked the induction of altered DNA methylation. Our findings argue that DNA methylation alterations that occur in gastric mucosae after HP infection are composed of transient components and permanent components, and that it is the infection-associated inflammatory response, rather than HP itself, which is responsible for inducing the altered DNA methylation. Cancer Res; 70(4); 1430–40